(untitled) (Journal of Informatics and Mathematical Sciences, 2017)
In this paper, we prove some basic properties of \(k\)-quasi-\(^*\)parahyponormal operators and spectrum of class of \(k\)-quasi-\(^*\)parahyponormal operators is continuous. Also, we proved the non zero points of its approximate point spectrum and joint approximate point spectrum are identical.